Evidence of interface dominated photovoltaic effect of Pt-sandwiched polycrystalline BiFeO3 thin film capacitors. (July 2015) - Peng, Zengwei; Wang, Yinglong; Liu, Baoting
Abstract: Photovoltaic (PV) effects of Pt sandwiched polycrystalline BiFeO3 (BFO) thin films deposited directly on Pt(111)/Ti/ SiO2 /Si(001) substrate at 550 °C by radio frequency magnetron sputtering are investigated under different BFO film thicknesses. It is found that both 300 and 450 nm thick BFO thin films do not exhibit obvious PV effects, which can be attributed to their large leakage current density. However, obvious PV effects are observed in the samples of 600 and 750 nm in thickness. It is found that not only the open circuit voltage but also the short circuit current density of the two samples decreases with the increasing annealing temperature on top Pt/BFO interfaces. The obtained PV results can be explained by the change of the interface state induced by the high temperature thermal treatment.